Microbiological reasoning of the formation and development of vulvovaginal candidiasis - N. D. Yakovychuk; S. Ye. Dejneka; L. I. Sydorchuk; D. V. Rotar; I. Y. Sydorchuk; V. B. Popovych (Zaporožskij Medicinskij Žurnal)
Aim. To conduct microbiological reasoning of the formation and development of vulvovaginal candidiasis. To study taxonomic composition and major microbiota and yeast-like fungi of genus Candida and their changes in vulvovaginal content of women with vulvovaginal candidiasis.